Dimensions of private law: Categories and concepts in Anglo-American legal reasoning - Waddams, Stephen (Cambridge University, 2013)
Anglo-American private law has been a far more complex phenomenon than has been usually recognized. This study will be of importance to those interested in property, tort, contract, unjust enrichment, legal reasoning, legal method, the history of the common law, and the relation between legal theory and legal history.